The Analysis of the Competitiveness of the Regional Road Transport Sector Using the Environmental Scenario Method - Tomasz BUDZIK (Communications of International Proceedings, 2021)
Enterprises wishing to succeed must predict the ways for their conduct in the future. This takes into account the conditions created by the environment, in which the opportunities to exploit and threats to avoid are searched for. For this purpose, the appropriate tools are used.  One of them is the environmental scenario analysis. In the article, the use of the environmental scenario method is presented, in relation to the public regional road transport sector. On the basis of own forecasts, future scenarios determining the achievement of success in this market were specified. These forecasts were based on the updated results of the author’s previous research.
Keywords: Regional Transport; Environmental Scenario Method; Sector Analysis; PKS; Car Communication Enterprises